Plant–frugivore interactions across the Caribbean islands: Modularity, invader complexes and the importance of generalist species - Vollstädt, Maximilian G. R.; Galetti, Mauro [UNESP]; Kaiser-Bunbury, Christopher N.; Simmons, Benno I.; Gonçalves, Fernando; Morales-Pérez, Alcides L.; Navarro, Luis; Tarazona-Tubens, Fabio L.; Schubert, Spencer; Carlo, Tomas; Salazar, Jackeline; Faife-Cabrera, Michel; et al. (Wiley, 2022)
Aim: Mutualistic interactions between plants and animals are fundamental for the maintenance of natural communities and the ecosystem services they provide. However, particularly in human-dominated island ecosystems, introduced species may alter mutualistic interactions. Based on an extensive dataset of plant–frugivore interactions, we mapped and analysed a meta-network across the Caribbean archipelago. Specifically, we searched for subcommunity structure (modularity) and identified the types of species facilitating the integration of introduced species in the Caribbean meta-network. Location: Caribbean archipelago (Lucayan archipelago, Greater Antilles, Lesser Antilles). Methods: We reviewed published scientific literature, unpublished theses and other nonpeer-reviewed sources to compile an extensive dataset of plant–frugivore interactions. We visualized spatial patterns and conducted a modularity analysis of the cross-island meta-network. We also examined which species were most likely to interact with introduced species: (1) endemic, nonendemic native or introduced species, and (2) generalized or specialized species. Results: We reported 3060 records of interactions between 486 plant and 178 frugivore species. The Caribbean meta-network was organized in 13 modules, driven by a combination of functional or taxonomic (modules dominated by certain groups of frugivores) and biogeographical (island-specific modules) mechanisms. Few introduced species or interaction pairs were shared across islands, suggesting little homogenization of the plant–frugivore meta-network at the regional scale. However, we found evidence of “invader complexes,” as introduced frugivores were more likely to interact with introduced plants than expected at random. Moreover, we found generalist species more likely to interact with introduced species than were specialized species. Main conclusions: These results demonstrate that generalist species and “invader complexes” may facilitate the incorporation of introduced species into plant–frugivore communities. Despite the influx of introduced species, the meta-network was structured into modules related to biogeographical and functional or taxonomic affinities. These findings reveal how introduced species become an integral part of mutualistic systems on tropical islands.
Keywords: Antilles; biotic interactions; frugivory; introduced species; invader complex; island ecosystems; species networks; West Indies